2013
DOI: 10.1371/journal.pone.0065868
|View full text |Cite
|
Sign up to set email alerts
|

Global Profiling in Vestibular Schwannomas Shows Critical Deregulation of MicroRNAs and Upregulation in Those Included in Chromosomal Region 14q32

Abstract: BackgroundVestibular schwannomas are benign tumors that arise from Schwann cells in the VIII cranial pair and usually present NF2 gene mutations and/or loss of heterozygosity on chromosome 22q. Deregulation has also been found in several genes, such as ERBB2 and NRG1. MicroRNAs are non-coding RNAs approximately 21 to 23 nucleotides in length that regulate mRNAs, usually by degradation at the post-transcriptional level.MethodsWe used microarray technology to test the deregulation of miRNAs and other non-coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 64 publications
2
35
0
Order By: Relevance
“…Identification of new molecules involved in VS growth is of crucial importance to develop novel therapeutic strategies for this disease. Although Torres-Martin et al (2013) reported decreased expression of miR-1 in human VS tissues in 2013, its effect on VS cell growth and associated molecular mechanisms have not yet been described. In the present study, we confirmed the down-regulation of miR-1 in VS specimens, with this phenomenon being particularly noticeable in those isolated from large tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of new molecules involved in VS growth is of crucial importance to develop novel therapeutic strategies for this disease. Although Torres-Martin et al (2013) reported decreased expression of miR-1 in human VS tissues in 2013, its effect on VS cell growth and associated molecular mechanisms have not yet been described. In the present study, we confirmed the down-regulation of miR-1 in VS specimens, with this phenomenon being particularly noticeable in those isolated from large tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA quality was assessed by formaldehyde agarose gel electrophoresis and quantified spectrophotometrically. The GeneChip miRNA 1.0 array (Affymetrix, Santa Clara, CA) with coverage of miRBase v.11 was used in this study according to a previously described method . Details are provided in the Supporting Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest chr19_34670 as a tumor suppressor in VS. Other candidate miRNAs identified in our study have been previously documented with the indicated capabilities in various tumors. For instance, miR-183 was found to be decreased in melanomas and schwannomas compared with local normal tissues or normal nerves [25,27]. This indicates the reliability of high-throughput sequencing platform for proliferation phenotype analysis and the potential important role of miRNAs in VS cell proliferation.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, overexpression of miR-21 promotes VS growth by downregulating PTEN [22]; miR-7 functions as a tumor suppressor by targeting the EGFR, Pak1 and Ack2 oncogenes; and let-7d (a let-7 family member) is upregulated in both schwannomas and meningiomas [23,24]. Furthermore, recently, evidence showed global upregulation of the 14q32 chromosomal site, which contains miRNAs associated with VS formation and/or maintenance [25]. However, no evidence of a functional role for miRNAs in CVS has been documented to date.…”
Section: Introductionmentioning
confidence: 99%